Narodowy projekt „Szansa na powrót” jako sposób społecznej reintegracji skazanych ze społeczeństwem - Valentovičová, Zuzanna; Jasiński, Krzysztof (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
In this presentation, the authors deal with specialised prison sentence execution with an emphasis on the penitentiary treatment with convicts in exit units in the Slovak Republic. They draw attention to the implementation of innovative elements in the process of penitentiary treatment and the preparation of convicts for their life after release from prison.
Keywords: skazany; wykonanie kary pozbawienia wolności; leczenie penitencjarne; zwolnienie; opieka postpenitencjarna; Szansa na powrót; resocjalizacja